Multipotentials in educational discourse - Maryna Petrovna Prepotenska (Філософія освіти, 2020)
While responding to the challenges of globalization, the system of modern education often reduces the range of humanitarian disciplines, forming utilitarian programs in universities, but at the same time preserves such a vestige of the past as the priority of the academic format over the heuristic one. At the same time, the global world, a multiplex of events and opportunities, contributes to the emergence of a special type of a student in the educational discourse – a multipotential (MPL), who is capable of succeeding in several activities at once. The philosophical and methodological key to the reorganization of education within this context may be the idea of ​​a “transversal self” of a student in the dynamics of diversity and creative self-development. In light of the theory of generations and multipotentiality, a balance of academism and new forms of university communication is becoming necessary because in the life of millennials and representatives of generation Z, reality and virtual space, modular thinking and multitasking, the dislike for reading and creativity, and independent judgments merge. Interactive, visual, virtual and performative forms of learning are the most effective solutions for them. Social cataclysms of the beginning of the 21st century also require special stress resistance, emotional intelligence, auto-reflection, and media literacy from participants of the educational process. This actualizes the resources of practical philosophy, psychology, sociology and other humanitarian disciplines for the comprehensive development, awareness and self-regulation of a person. A very constructive educational discourse is the communication of a multi-potential teacher with gifted students. One example can be the scientific and creative activities of Vanya Angelova, a professor at Velikotyrnovsky University. St. Cyril and Methodius, who emphasizes the value of the "return" of the book, the co-creation of teachers and students, and wide international cooperation within the context of the topic of multi-potentials.